An inticetus-like (Cetacea: Odontoceti) postcanine tooth from the pietra leccese (Miocene, Southeastern Italy) and its palaeobiogeographical implications - Peri E.; Collareta A.; Insacco G.; Bianucci G. (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen, 2019)
We report on an isolated cetacean postcanine tooth that was collected close to the village of Melpignano (Lecce Province, Apulia region) from the Miocene “Pietra leccese” formation of south-eastern Italy. This tooth exhibits a transversely compressed and roughly semi-circular crown featuring several large, broad-based accessory denticles that are arranged radially. Dental enamel ornamentation is limited to faint subvertical grooves, and a slight subvertical incision just below the base of the crown suggests that it was double-rooted. Our comparisons allow us to identify the Melpignano specimen as belonging to a heterodont dolphin close to Inticetus vertizi, the only named member of the archaic odontocete family Inticetidae, which has been recently described from Burdigalian (early Miocene) strata of the Chilcatay Formation of southern Peru. This find highlights the elusive presence of Inticetus-like toothed whales in the Mediterranean region during the Miocene. We then review the geographic distribution of fossil remains of Inticetus-like cetaceans, which includes records from the Miocene of Peru, North Carolina (eastern U.S.A.), the Atlantic coast of France, and south-eastern Italy. We hypothesise that inticetids dispersed via the Central American Seaway, which allowed faunal interchanges between the south-eastern Pacific and the northern Atlantic/Mediterranean realms until latest Miocene times. In conclusion, the finding of an Inticetus-like tooth in Miocene beds in Italy suggests that our knowledge on the past distribution of inticetid cetaceans is far from being exhaustive.